Off-label despite high-level evidence: a clinical practice review of commonly used off-patent cancer medicines - Zarkavelis, George; Amylidi, A. L.; Verbaanderd, C.; Cherny, N. I.; Metaxas, Y.; de Vries, E. G. E.; Zygoura, P.; Amaral, T.; Jordan, Karin; Strijbos, M.; Dafni, U.; Latino, N.; et al. (ESMO open, 2023)
Introduction - Off-label use of medicines is generally discouraged. However, several off-patent, low-cost cancer medicines remain off-label for indications in which they are commonly used in daily practice, supported by high-level evidence based on results of phase III clinical trials. This discrepancy may generate prescription and reimbursement obstacles as well as impaired access to established therapies. - Methods - A list of cancer medicines that remain off-label in specific indications despite the presence of high-level evidence was generated and subjected to European Society for Medical Oncology (ESMO) expert peer review to assess for accountability of reasonableness. These medicines were then surveyed on approval procedures and workflow impact. The most illustrative examples of these medicines were reviewed by experts from the European Medicines Agency to ascertain the apparent robustness of the supporting phase III trial evidence from a regulatory perspective. - Results - A total of 47 ESMO experts reviewed 17 cancer medicines commonly used off-label in six disease groups. Overall, high levels of agreement were recorded on the off-label status and the high quality of data supporting the efficacy in the off-label indications, often achieving high ESMO-Magnitude of Clinical Benefit Scale (ESMO-MCBS) scores. When prescribing these medicines, 51% of the reviewers had to implement a time-consuming process associated with additional workload, in the presence of litigation risks and patient anxiety. Finally, the informal regulatory expert review identified only 2 out of 18 (11%) studies with significant limitations that would be difficult to overcome in the context of a potential marketing authorisation application without additional studies. - Conclusions - We highlight the common use of off-patent essential cancer medicines in indications that remain off-label despite solid supporting data as well as generate evidence on the adverse impact on patient access and clinic workflows. In the current regulatory framework, incentives to promote the extension of indications of off-patent cancer medicines are needed for all stakeholders.